The Flame of Sinai: Hope and Vision in Iqbal by Sheila McDonough (Lahore: Iqbal Academy Pakistan, 2002, 249 pages.) (American Journal of Islam and Society, 2004)
The current surge of attention and sensitivity to Islam in western academiaand popular culture often boils down to the question of Islam’s compatibility– or lack thereof – with modernity. The issue is by no means a simpleone, and is further complicated by the fact that both “Islam” and “modernity”are made to carry a heavy load of multiple definitions that are alsosusceptible to ideological uses and abuses. Such influential American commentatorsas Francis Fukuyama, Daniel Pipes, and Bernard Lewis havebeen unanimous in their diagnosis that while Judaism and Christianity havecome to terms with modernity, Islam has so far failed to take that necessaryand crucial step. In the larger context of modern Muslim history, however,the question is almost two centuries old; it was repeatedly grappled with inthe past and continues to occupy a prominent place in the Muslim consciousness.Sheila McDonough’s new book on Muhammad Iqbal (1877-1938) can be approached with reference to this particular discourse, for thequestion of Islam and modernity was perhaps the most important factor thatmotivated and shaped Iqbal’s creative output – a body of ideas whose revelancehas tremendously increased in the six decades since his death.While Iqbal’s poetic and intellectual genius has been greatly celebratedand widely acclaimed, both within the Indian subcontinent and abroad, it canbe safely contended that his true potential as the twentieth century’s mostimportant post-critical Muslim philosopher is yet to be discovered. In view ofhis work’s creativity, depth, and visionary reach, the number and quality ofEnglish-language studies on Iqbal’s thought leave much to be desired. In thiscontext, McDonough has done a remarkable service by making the intellectualand imaginal contours of Iqbal’s consciousness accessible to a new generationof Muslim and non-Muslims readers, many of whom have been recentlysensitized to the question of Islam’s relationship with modernity. Mixing herserious erudition with a loving sensitivity and an almost artistic gift for discerninginterconnections, McDonough skillfully blends together the accountsof the vicissitudes of Iqbal’s personal life, his turbulent socio-historical context,and his sometimes shocking ideas to paint a colorful picture of his life,times, vision, and struggle. The Flame of Sinai is sure to become a classic,alongside a similar work by another Western admirer of Iqbal, namely, the lateAnnemarie Schimmel’s book Gabriel’s Wing. Incidentally, both of thesecharming titles come from Iqbal’s own symbolic imagination ...